2011
DOI: 10.1007/s10552-011-9731-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of body size and reproductive factors with circulating levels of sex hormones and prolactin in premenopausal Japanese women

Abstract: The data suggest that an increased risk of premenopausal breast cancer associated with low BMI is partially mediated by an increased total estradiol. Androgens and prolactin may explain the breast cancer protection provided by giving birth and breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 41 publications
9
33
3
Order By: Relevance
“…Regarding reproductive factors, in line with numerous previous reports, we found that prolactin levels among parous women were lower than those among nulliparous women (6,(9)(10)(11). Furthermore, the observed gradual decrease in prolactin levels with increasing number of FTP is in agreement with some studies (11, 37), but not with other studies, where the parity related decrease was only related to the first FTP (6,9,10).…”
Section: Cancer Epidemiol Biomarkers Prev; 23(11) November 2014supporting
confidence: 92%
See 1 more Smart Citation
“…Regarding reproductive factors, in line with numerous previous reports, we found that prolactin levels among parous women were lower than those among nulliparous women (6,(9)(10)(11). Furthermore, the observed gradual decrease in prolactin levels with increasing number of FTP is in agreement with some studies (11, 37), but not with other studies, where the parity related decrease was only related to the first FTP (6,9,10).…”
Section: Cancer Epidemiol Biomarkers Prev; 23(11) November 2014supporting
confidence: 92%
“…Recent epidemiologic data suggest that higher circulating prolactin levels are associated with increased risk of breast cancer (3)(4)(5), and several potential breast cancer risk factors have been examined in relation to circulating prolactin levels (6)(7)(8)(9), although these latter results are inconsistent. Regarding reproductive factors, it is well known that women who have experienced a full-term pregnancy (FTP) have lower levels of prolactin compared with women who have not been pregnant (6,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…However, some large studies have succeeded in detecting associations between potential breast cancer risk factors and sex hormone levels using untimed blood samples (45)(46)(47). We also confirmed some of these associations in our dataset (34,35). We cannot rule out the possibility that In conclusion, we observed an inverse association between acrylamide intake and total and free estradiol levels and a positive association between acrylamide intake and FSH levels in premenopausal Japanese women.…”
Section: Discussionsupporting
confidence: 56%
“…Because 43 women did not respond to the dietary questionnaire, remaining 393 women ages 20 to 54 years comprised the study population. These women had been previously examined for relationships among body size, reproductive factors, dietary factors, and hormone levels (34,35).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation